Analysis of metals and metalloid in commercial fish species from the Galapagos Marine Reserve: Toxicological and nutritional assessment. (April 2023) - Franco-Fuentes, Eduardo; Moity, Nicolas; Ramírez-González, Jorge; Andrade-Vera, Solange; Hardisson, Arturo; Rubio, Carmen; Paz, Soraya; González-Weller, Dailos; Rubio, Carmen; Gutiérrez, Ángel J.
Abstract: Aquatic pollution derived from metal presence in the Galapagos Islands could affect biodiversity and human health. This research provide a baseline on food safety in commercial fish species of the Galapagos Islands. We sampled muscle tissue of pelagic ( Acanthocybium solandri ) and demersal ( Caulolatilus affinis, Pontinus clemensi, Hyporthodus mystacinus, and Paralabrax albomaculatus ) species. Metal and metalloid concentrations per species were analyzed by Inductively Coupled Plasma Optical Spectrometry (ICP-OES). According to the Food and Agriculture Organization (FAO) regulation none of the studied species should be ingested; and according to the European Food Safety Authority (EFSA) regulation, all the studied species were above the Maximum Allowable Concentration (MAC) for Cd. According to EFSA, C. affinis should not be commercialized. Finally, A. solandri, P. clemensi and H. mystacinus do not represent a human health risk since its Margen of Safety (MoS) < 1 for people of up to 100 kg of body weight. Highlights: Pelagic species had higher concentrations of Zn than demersal species, while the latter have higher concentrations of K, Mg and Cr. Hyporthodus mystacinus had the lowest metallic concentrations of all the studied species. All studied species were above the Maximum Allowable Concentration (MAC) for Cd, while Caulolatilus affinis was the unique species that exceed the MAC for Pb. For the studied metals, Acanthocybium solandri, Pontinus clemensi and Hyporthodus mystacinus do not represent a risk to human health for people with < 100 kg of body weight since its MoS < 1. Paralabrax albomaculatus and Pontinus clemensi are good sources of Fe, Mg and Ca, while Acanthocybium solandri is a good source of Zn.